Laser cladding of Ti-6Al-4V with carbide and boride reinforcements using wire and powder feedstock - Farayibi, Peter Kayode (2014)
The growth in the use and wear of Ti-based alloy components in mining and offshore explorations has led to a search for techniques to re-engineer such components for reuse. The most desirable method of restoring/protecting the component surfaces is by hard-facing to enhance longevity in service.